Supplementary feeding utilizing climate-smart indigenous vegetables from school gardens with iron fortified rice improved nutritional status of schoolchildren - Agdeppa, Imelda Angeles (Philippine Journal of Science, 2018)
This study evaluated the effectiveness of supplementary feeding in improving weight, vitamin A (VA), and hemoglobin levels of children using vegetables from school gardens and iron fortified rice (IFR). A cluster randomized controlled study using multi-stage sampling involving 6–8 year old underweight (WAZ <–2 SD) and/or anemic (hemoglobin <12 g/dL) schoolchildren in three public schools in Cavite province was conducted. School 1 and School 2 received lunch with standardized one-dish vegetable recipe; however, School 1 and School 2 had IFR (GIFR) and ordinary rice (GOR), respectively. School 3 (SNK) served hot soups or native delicacies as snacks available in the school canteen. Eighty (80) children in each group participated in the feeding every school day, 5 days a week for 120 days. Data on weight, hemoglobin, and serum retinol concentration for vitamin A (VA) levels were collected before and after the study using standard methods. Basal and endpoint mean weight was similar between groups; however, within group mean increment was significantly higher in GIFR and SNK than in GOR (p<0.05). Translating the results to prevalence of underweight at endpoint, the decrease in GOR was significantly higher than the decrease in GIFR and SNK (p<0.05). Basal mean hemoglobin levels were similar between groups; at endpoint, mean increment in GIFR 1 was significantly higher than in GOR. Baseline prevalence of anemia was significantly lower in SNK than in the two schools (p=0.05). At endpoint, only GIFR had a significant decline between time periods (p=0.000). Baseline mean VA was significantly lower in GIFR than in SNK (p=0.027); at endpoint, mean level was significantly higher in GIFR than in SNK (p=0.003). Supplementary feeding is effective in improving the weight of schoolchildren. The model of linking the use of vegetables from school garden had improved VA levels and the use of IFR has increased hemoglobin level.